Konsep Fikih Ikhtilaf Yusuf al-Qaradhawi - Mohammad Hanief Sirajulhuda (Universitas Darussalam Gontor, 2017)
This article describes the jurisprudence concept of Yusuf al-Qaradawi. The author tries to solve the problems related to the division of the ummah due to the misunderstanding of the various ikhtilâf of fqh that occurred among Moslem scholars. A full and correct understanding will not cause this people divided. On the contrary, Moslems will maintain tolerance and unity in diversity. Therefore, Yusuf al-Qaradawi offers his concept of jurisprudence which is described in detail by the authors in this article. Yusuf al-Qaradawi offers the implementation of the concept of Jurisprudence in ten ways. First, accepting the difference in furu’ as necessity, grace, and discretion. Second, working on the great problems that people face todays. Yusuf al-Qaradawi reveals, the great problems facing Muslims today include the backwardness of science, technology and civilization, socio-economic imbalances, dictatorship and arbitrariness of politics, westernization and ghazw al-fkr, hostility and occupation of Zionism, disunity and dispute in the Arab and Islamic world, as well as moral decadence. Third, examine the opinions of the Moslem scholars. Fourth, following the middle manhaj and leaving the attitude excessive in religion. Fifth, prioritizing muhkamât, not mutasyâbihât. Sixth, not confrming and refusing ijtihâdiyyah matters. Seventh, defning the terms and meanings. Eighth, cooperating on an agreed issue. Ninth, having tolerance in disputed matters. And tenth, refraining from those who admit lâ ilâha illallâh.